2010
DOI: 10.1260/1747-9541.5.4.503
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Typology of Abusive Coaching Behaviours within Youth Sport

Abstract: The purpose of this article was to create the Typology of Coaching Transgressions model (TOCT), which is concerned with abuse, neglect and violence in youth sport. Comments provided by the Justplay Behaviour Management Program from two competitive hockey associations and one large soccer association were analyzed and sorted to assess the utility of the model to capture inappropriate coaching behaviours. A total of 540 comments were examined deductively using the TOCT. Approximately 80% of coaching transgressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 24 publications
2
37
1
1
Order By: Relevance
“…A total of 652 cases were recorded in 2011. The data support the argument that abuse in sport can take a range of forms (Raakman et al ., ). The data highlighted that the allegations came from a range of sources and were related to a variety of safeguarding concerns.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A total of 652 cases were recorded in 2011. The data support the argument that abuse in sport can take a range of forms (Raakman et al ., ). The data highlighted that the allegations came from a range of sources and were related to a variety of safeguarding concerns.…”
Section: Resultsmentioning
confidence: 97%
“…Raakman et al . () have outlined that abuse in sport can take a range of forms including sexual, physical, emotional, neglectful and poor practice. There has been a growing body of research into abusive relationships in sport over the past decade.…”
Section: Abuse In Sportmentioning
confidence: 99%
“…The only large-scale study available is from the UK, which reported a prevalence of psychological abuse of 75%, raising concerns that this may be the most urgent safeguarding concern in youth sport 38 39. Psychologically abusive behaviours described by athletes generally reflect those described by the WHO and the UN Convention on the Rights of Children 35 38 40 41. Athletes report: belittling, humiliating, shouting, scapegoating, rejecting, isolating and threatening behaviours as well as being ignored, or denied attention and support 24 26 38 42 43…”
Section: Forms Of Abuse and Harassment In Sportmentioning
confidence: 99%
“…Exploitation of power differentials between a performer and coach has frequently been identified in the perpetration of the mistreatment of children (Fasting et al ., 2018; McMahon et al ., 2018; Parent and Demers, 2011; Stafford et al ., 2015). In some instances, the sports coach has been identified as having greater influence over children than other significant adults (Raakman et al ., 2010).…”
Section: Research Context: the Culture Of Child Abuse In Sport – Powementioning
confidence: 99%